Lateralidad y su incidencia en el proceso de la lecto-escritura de los niños y niñas de primero inicial de la Unidad Educativa Francisco Huerta Rendón en la ciudad de Babahoyo - Delgado Cruz, Nohely Susana (2022)
Boys and girls with defined laterality obtain better development in their reading-writing skills. In laterality it is mentioned that people tend to have an inclination for a part of their body, that is, they do not only manipulate their hands but also their extremities together with their sensory organs. Both the right and left hemispheres are responsible for the inverted motor domain. In addition, within laterality there are right-handed, left-handed, ambidextrous, it is possible that there are people with crossed lateral predominance and their lateralization is not the same. The reading-writing processes provide the child with the ability to read and write, but this process does not take place, nor does it occur easily, if it does not consist of a good development of laterality. In other words, it is essential since it will be the promoter of social relations, who understands and issues opinions, will cover the child's intellectual development at all times. The importance, the levels, and the methods that are used in initial education for reading and writing are mentioned. There are methods within their teaching that their application can cause a disadvantage since it is not given properly and causes the child to lose interest in learning. That is why a sample population of 38 students was taken into account, where it was determined that laterality does significantly influence the literacy processes of children in the first level of Initial belonging to the Francisco Huerta Rendon Educational Unit.